The Nazi Olympics : Berlin 1936 / Susan D. Bachrach. - Bachrach, Susan D, 1948- (Little, Brown, 2000)
Recounts the story of the Olympics held in Berlin in 1936, and how the Nazis attempted to turn the games into a propaganda tool for their cause